The Role of AI in ASN Leadership Succession Planning in Nias Regency Government - Putera Ndraha, Marlansyah; Ndraha, Ayler Beniah; Magdalena Bate'e, Maria; Mendrofa, Yupiter; Kurniawan Telaumbanua, Elisati (Dinasti Publisher, 2024)
This research aims to evaluate the role of artificial intelligence (AI) in leadership succession planning of the State Civil Apparatus (ASN) in the Nias Regency Government. A combination of qualitative and quantitative research methods was used, with in-depth interviews and analysis of performance data using AI. The research was conducted from July to August 2024 at the Office of the Regent of Nias, North Sumatra. The results showed that the application of AI improved efficiency and objectivity in the succession process, with AI's ability to deeply analyze ASN performance data and identify the right candidates for promotion. However, challenges such as limited resources, additional training needs, and data management must be overcome. The conclusion of this study is that AI can improve leadership succession planning in Nias Regency Government by increasing efficiency and reducing bias, provided that implementation challenges are properly addressed.